2016
DOI: 10.1007/s10518-016-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

The Reticulatus method for shear strengthening of fair-faced masonry

Abstract: This paper presents the results of several experimental campaigns recently carried out by the authors and devoted to the investigation of the mechanical performance of wall panels strengthened by applying repointing mortar and high strength stainless steel or composite cords. The reinforcement system, known as Reticulatus, allows the reinforcement of regular and irregular-shape masonry walls, when the fair-faced aspect must be kept. In the perspective of using this reinforcement method, this article summarizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Besides the difference of improvement on retrofitting materials, the improvement of same retrofitting material on different masonry structures varies as well. [64] found that the shear strength of the retrofitted pebble masonry was improved about 40% while 17% for stone masonry by using the same retrofitting technique. As this reinforcing system can keep the original aesthetic of the building, it is therefore suitable in reinforcing the fair-face masonry or the masonry heritages.…”
Section: Reticulatus Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides the difference of improvement on retrofitting materials, the improvement of same retrofitting material on different masonry structures varies as well. [64] found that the shear strength of the retrofitted pebble masonry was improved about 40% while 17% for stone masonry by using the same retrofitting technique. As this reinforcing system can keep the original aesthetic of the building, it is therefore suitable in reinforcing the fair-face masonry or the masonry heritages.…”
Section: Reticulatus Systemmentioning
confidence: 96%
“…After that, the reinforcement and anchoring bars will be covered by re-pointing mortar back to the joints. The dimension of the reinforcement mesh normally ranges from 300-500mm, and it must be smaller than the thickness of the panel [64]. The detailed configuration of a typical reticulatus system is displayed in Fig.…”
Section: Reticulatus Systemmentioning
confidence: 99%
“…In order to improve the effectiveness of the metal reinforcements, new materials and methods have been experimented. An example is the use of ultra-high strength steel fibres [9][10][11][12][13] and stainless steel profiles [14][15][16][17][18]. Composite materials continued to be used for historic masonry reinforcement, but their application was made not with epoxy adhesives, but with metal fasteners or inorganic (lime-or cement-based) mortars [19][20][21][22][23].…”
Section: Materials Properties and Civil Applicationsmentioning
confidence: 99%
“…On the efficacy and potential for use of innovative materials such as FRP or UHTSS, high strength stainless steels, applied in the form of a grid (Reticulatus System) in the field of seismic retrofit of masonry walls belonging to historical buildings, it has been widely written in the specific scientific literature [20][21][22][23][24][25][26][27]. The traditional timber frame reinforcements can be effectively replaced by a homologous frame, according to a similar geometric pattern, composed of natural basalt fiber strips, arranged in adherence to the wall front and glued to the wall itself by means of a GeoCalce (a KeraKoll patent), a hydraulic lime matrix compatible with the traditional binder present in the walls (Fig.…”
Section: Natural Basalt Fiber Strips System (Bfrp)mentioning
confidence: 99%